Interactions of polymorphisms in different clock genes associated with circadian phenotypes in humans - Mario Pedrazzoli; Rodrigo Secolin; Luiz Otávio Bastos Esteves; Danyella Silva Pereira; Bruna Del Vechio Koike; Fernando Mazzili Louzada; Iscia Lopes-Cendes; Sergio Tufik (Genetics and Molecular Biology, 2010)
Several studies have shown that mutations and polymorphisms in clock genes are associated with abnormal circadian parameters in humans and also with more subtle non-pathological phenotypes like chronotypes. However, there have been conflicting results, and none of these studies analyzed the combined effects of more than one clock gene. Up to date, association studies in humans have focused on the analysis of only one clock gene per study. Since these genes encode proteins that physically interact with each other, combinations of polymorphisms in different clock genes could have a synergistic or an inhibitory effect upon circadian phenotypes. In the present study, we analyzed the combined effects of four polymorphisms in four clock genes (Per2, Per3, Clock and Bmal1) in people with extreme diurnal preferences (morning or evening). We found that a specific combination of polymorphisms in these genes is more frequent in people who have a morning preference for activity and there is a different combination in individuals with an evening preference for activity. Taken together, these results show that it is possible to detect clock gene interactions associated with human circadian phenotypes and bring an innovative idea of building a clock gene variation map that may be applied to human circadian biology.